Tertiary EFL Lecturer’s Assessment Beliefs and Practices in English Listening - Yustika Sari; Yulianah Sain; Faridawati Faridawati (Universitas Pahlawan Tuanku Tambusai, 2026)
Listening assessment plays an important role in supporting effective language learning and evaluating students’ listening proficiency in EFL classrooms. However, limited research has examined how lecturers’ beliefs about listening assessment are reflected in their actual classroom practices, particularly in Indonesian higher education contexts. This study aims to investigate an EFL lecturer’s beliefs about listening assessment and how these beliefs are enacted in classroom assessment practices at Muhammadiyah University of Kendari. A qualitative case study design was employed involving one experienced EFL lecturer who taught English listening courses and was responsible for designing and implementing listening assessments. Data were collected through classroom observations, semi-structured interviews, and document analysis and were analyzed using thematic analysis. The findings reveal that the lecturer believes listening assessment should be fair, reliable, valid, and accountable. These beliefs are reflected in the implementation of diagnostic, formative, and summative assessments, the use of varied assessment techniques, and the selection of authentic and credible listening materials aligned with learning objectives. The study concludes that there is a strong alignment between the lecturer’s assessment beliefs and classroom practices. These findings contribute to a better understanding of listening assessment in higher education and provide practical insights for EFL lecturers seeking to develop more effective and consistent assessment practices.